Mullerian Adenosarcoma of Uterus and Cervix- A Report of Four Cases with Review of Literature - Ebenezer, Evelyn Elizabeth; Shah, Saloni Naresh; Geetha, N (Annals of Pathology and Laboratory Medicine, 2022)
Uterine sarcomas are rare female genital tract malignancies. Mullerian adenosarcoma is a rare biphasic malignant mesenchymal tumor comprising of a benign glandular and malignant (usually low grade) stromal component, both of which are integral and neoplastic constituents of the tumor.[1] This tumor represents less than 8% of uterine sarcomas. About 200 cases have been reported in the literature so far [2] of which 22 case were from India. Adenosarcomas are usually low grade. Sarcomatous overgrowth is defined as the presence of sarcomatous component is more than 25% of the tumor volume. High grade morphology was termed adenosarcoma with sarcomatous overgrowth (i.e, presence of pure sarcoma , without epithelial component comprising 25% of the tumor).The features of high grade sarcomatous overgrowth include severe nuclear pleomorphism, prominent nucleoli , increased mitotic activity and necrosis[2]. Herein, we present four cases of adenosarcoma of the uterine corpus and cervix, discuss their clinico-pathological findings in detail and add a note on the recent and evolving concepts